2005
DOI: 10.1071/aj04040
|View full text |Cite
|
Sign up to set email alerts
|

Seabed Sediment Transport and Offshore Pipeline Risks in the Australian Southeast

Abstract: The Australian seabed is influenced by extreme weather conditions of various types: cyclones, high tidal ranges, offshore currents and storm waves. In the past two centuries substantial progress in our understanding of the seabed and environmental conditions has been made by studies of the seabed sedimentology, hydrodynamics, and through habitat mapping. As part of the CSIRO Wealth from Oceans Flagship program the authors are involved in a new fiveyear study to investigate and predict the effect of possible cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Therefore, when seawater leaves the Bass Strait on its eastern side, it has a prominent density contrast against the Tasman Sea water (Tomczak, 1985). As a consequence, warm, denser Bass Strait seawater can flow into and sink beneath the cooler, fresher water of the Gippsland shelf, generating the northeast flowing "Bass Cascade Current" which sinks to the 200-400 m isobaths and extends more than tens of kilometres (Figure 2B; Godfrey et al, 1980;Li et al, 2005;Mitchell et al, 2007b). Observations from the ocean bottom stations have revealed that the BCC has transported significant quantities of water and spreads along the shelf edge over a long distance (Boland, 1971).…”
Section: Climate and Oceanographymentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, when seawater leaves the Bass Strait on its eastern side, it has a prominent density contrast against the Tasman Sea water (Tomczak, 1985). As a consequence, warm, denser Bass Strait seawater can flow into and sink beneath the cooler, fresher water of the Gippsland shelf, generating the northeast flowing "Bass Cascade Current" which sinks to the 200-400 m isobaths and extends more than tens of kilometres (Figure 2B; Godfrey et al, 1980;Li et al, 2005;Mitchell et al, 2007b). Observations from the ocean bottom stations have revealed that the BCC has transported significant quantities of water and spreads along the shelf edge over a long distance (Boland, 1971).…”
Section: Climate and Oceanographymentioning
confidence: 99%
“…The Bass Cascade Current (BCC) is a high-energy, seasonal (especially in winter) phenomenon. When it flows through the Bass Strait, it is further fed by the Leeuwin current (LC), Zeehan current (ZC) and the wind stress within the Bass Strait, jointly transporting Bass Strait water towards the front (Li et al, 2005;Mitchell et al, 2007b).…”
Section: Climate and Oceanographymentioning
confidence: 99%
See 2 more Smart Citations
“…The Southern and Central regions of the Gippsland Basin are influenced by the seasonal Bass Cascade Current (BCC) (Figure 1A, 1C;Mitchell et al, 2007b). The BCC was formed due to the cold, denser Bass Strait seawater flowing into and sinking beneath the warmer, fresher water of the Gippsland shelf, generating a northeast flowing current and sinking to the 200 m isobath (Godfrey et al, 1980;Li et al, 2005;Mitchell et al, 2007b). The BCC is a high-energy current with an average transport rate of 3.6 km 3 /h (Godfrey et al, 1986).…”
Section: Oceanography and Climatementioning
confidence: 99%